THE STUDENTS’ ABILITY IN PRONOUNCING ENGLISH VOICED AND VOICELESS CONSONANTS BY USING MINIMAL PAIRS - Herlina, .; Novita, Dewi; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract : The purpose of this research is to investigate how well is the ability of  the Third Semester  Regular A Students of the English Education Study Program in Academic Year 2012/2013 in pronouncing voiced and voiceless consonants. Method of this research is descriptive study by holding three time of test using minimal pairs. Subject of this research is all of the Third Semester  Regular A Students of the English Education Study Program in Academic Year 2012/2013. Data of the research was collected by using pronouncing practice oral test of minimal pairs. Result of this research is the main score of students’ pronouncing ability at the first test was 91.37, the second test was 89.40 and the last test was 91.48 which was categorized as good to excellent. The result of the students’ mean score had shown their significant ability in pronouncing English voiced and voiceless consonants. Key word : Pronouncing Voiced and Voiceless Consonants, minimal Pairs. Abstrak : Tujuan dari Penelitian ini adalah untuk mennyelidiki seberapa baik kemampuan mahasiswa Program Studi Pendidikan Bahasa Inggris Reguler A semester ketiga tahun pelajaran 2012/2013 dalam melafalkan konsonan voiced dan voiceless Bahasa Inggris menggunakan minimal pairs. Metode penelitian ini adalah studi deskriptif dengan melakukan tiga kali test menggunakan minimal pairs. Subjek penelitian adalah seluruh mahasiswa Program Studi Pendidikan Bahasa Inggris Reguler A Semester ketiga tahun pelajaran 2012/2013. Data penelitian didapatkan dengan menggunakan test lisan praktek pelafalan minimal pairs. Hasil dari penelitian ini adalah nilai rata-rata yang diperoleh mahasiswa pada test pertama adalah 91,37, test kedua 89,40 dan test terakhir 91,48 yang dikategorikan baik sampai dengan luar biasa. Hasil nilai rata-rata mahasiswa ini telah menunjukkan kemampuan signifikan mereka dalam melafalkan  konsonan voiced dan voiceless Bahasa Inggris. Kata Kunci : Pelafalan Voiced dan Voiceless Konsonan, Minimal Pairs